Predictors of medical student interest and confidence in research during training: a cross-sectional study - Klowak, Jennifer; Elsharawi, Radwa; Whyte, Robert; Costa, Andrew; Riva, John (Canadian Medical Education Journal, 2018)
Purpose: Research education and opportunities are an important part of undergraduate medical education. This study’s objectives were to determine students’ interest in research, student self-rated research skills and to assess potential predictors of research interest and confidence. Method: Stakeholder consultation and literature informed a 13-item cross-sectional survey. In 2014, all students enrolled in McMaster University’s School of Medicine in Ontario, Canada were sent three waves of an electronic survey. Results: The response rate was 81% (498 of 618). Most (n=445, 89%) endorsed prior research experiences. The majority of students (n=383, 86%) wanted more research education and opportunities. Higher rating of their supervisors’ understanding of research was associated with greater interest in research (OR=2.08; 95% CI=1.27–3.41). Home campus (distributed vs. main) was not a significant predictor of research interest. In our adjusted linear regression model, significant predictors of higher self-rated research ability included prior thesis work and higher self-rated knowledge gained in MD program. Conclusions: In a survey of a three-year medical school, medical student interest in further research education and opportunities was high and positively predicted by student-rated supervisors’ understanding of research, but not campus location. This study also identified several predictors of student self-rated research ability.